Diagnostic school in social work: assessment of humanistic potential - Dobrina O. A., Basova T. V. (Interactive science, 2017)
this article discusses the stages of psychosocial practice development in social work, which are presented by different schools and approaches. The authors have analyzed the school with humanistic potential, which has a great importance in the modern world. The work also describes the interactions of a social worker with a client and the solution of his main social problems.
Keywords: социальная работа; клиент; социальный работник; social work; диагностическая школа; гуманистический потенциал; diagnostic school; humanistic potential; client; social worker